Body Image and Disordered Eating Among LGBTQ+ University Students and Recent Graduates in Rural Appalachia: A Thematic Analysis - Savitsky, Devyn (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
LGBTQ+ university students and recent graduates of a large rural Appalachian institution were interviewed for an exploratory thematic analysis on body image and disordered eating behaviors. While participants noted an overall sense of comfortability in the university setting, there were varying obstacles associated with navigating intersecting identities and physical presentation that were noted in the data. Excerpts from participant interviews were coded into five unique themes: (1) feeling "othered"/different from peers as well as fellow LGBTQ+ community members, (2) seeking comfortability with body/self, (3) facing stereotypes and image expectations based on presumed gender identity and/or sexual/affectional orientation, (4) general experiences as an LGBTQ+ community member in a rural university town, and (5) seeking increased support from the university. This study concludes that significant challenges related to body image are exacerbated by common experiences as a person in the LGBTQ+ community.